2005
DOI: 10.1158/0008-5472.can-04-4315
|View full text |Cite
|
Sign up to set email alerts
|

β1A Integrin Expression Is Required for Type 1 Insulin-Like Growth Factor Receptor Mitogenic and Transforming Activities and Localization to Focal Contacts

Abstract: The cells' ability to proliferate in response to growth factor stimulation is significantly altered during cancer progression. To investigate the mechanisms underlying these alterations in prostate cancer, the role and expression of B 1A integrin and type 1 insulin-like growth factor receptor (IGF-IR), known to contribute to cell proliferation and transformation, were analyzed. Using small interfering RNA oligonucleotides to down-regulate B 1A , we show that B 1A expression is required for IGF-IR-mediated pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 46 publications
4
85
0
3
Order By: Relevance
“…Recent studies have suggested that cooperation between IGF-IR and integrin signaling is necessary for the growth and migration of transformed cells (10,18). The data presented here indicate that the scaffolding protein RACK1 plays a central role in integrating this signaling through its interaction with PP2A, which is regulated by IGF-I and ␤1 integrin ligation.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Recent studies have suggested that cooperation between IGF-IR and integrin signaling is necessary for the growth and migration of transformed cells (10,18). The data presented here indicate that the scaffolding protein RACK1 plays a central role in integrating this signaling through its interaction with PP2A, which is regulated by IGF-I and ␤1 integrin ligation.…”
Section: Discussionmentioning
confidence: 51%
“…The characteristics of cells expressing this IGF-IR mutant suggest that integrin signaling is a necessary component of IGF-IR signaling in maintaining the transformed phenotype of these cells. An essential role for ␤1 integrin in IGF-I-mediated tumor growth in prostate cancer was also recently proposed (10).…”
mentioning
confidence: 97%
“…Since AR signaling suppresses the expression of β4, c-Met, and ErbB2 (84, 85), androgen withdrawal experiments have suggested that focal adhesion kinase, which is activated by multiple β1 integrins, promotes the expansion of tumor progenitor cells in mouse models of mammary and intestinal tumorigenesis (73)(74)(75). Finally, although not directly focusing on tumor progenitor cells, prior studies have emphasized a role for β1 integrins, but not for β4, in prostate cancer (37,(76)(77)(78)(79). Our observation that β4 signaling is dispensable for prostate development but not tumorigenesis is consistent with the hypothesis that tumor cells are exquisitely dependent on certain integrin signaling pathways, such as those activated by β4, whereas their normal counterpart are not (32,74).…”
Section: Figurementioning
confidence: 99%
“…During malignant progression, the complex crosstalk between the IGF axis and integrin signaling contributes to enhanced cell survival, proliferation, migration and invasion (Beattie et al, 2010). Studies by Goel et al (2004Goel et al ( , 2005 have shown that IGF-IR signaling and its mitogenic and transforming activities in prostate cancer cells are regulated by b1 integrin and this involves direct interaction between the two molecules. In addition, crosstalk between the integrin vitronectin receptor avb3 and the IGF-IR has been documented in various tumor cells (Clemmons and Maile, 2003), and the prosurvival effect of fibronectin in pancreatic carcinoma cells was shown to be mediated via IGF-IR and involve the b3 integrin (Edderkaoui et al, 2007).…”
Section: Lung Metastasismentioning
confidence: 99%